Occurrence and Identification of Root-Knot Nematodes on Red Dragon Fruit (Hylocereus polyrhizus) in Hainan, China - Haibo Long; Yuan Chen; Yueling Pei; Huadong Li; Yanfang Sun; Tuizi Feng (Agronomy, 2022)
The genus Meloidogyne is one of the most economically damaging plant parasitic nematodes on a worldwide basis. To date, only the dragon fruits in Brazil were reported infected by M. javanica or M. incognita in previous surveys. From 2019–2021, we conducted our investigation in 62 orchards from 10 counties of Hainan, which are the main producing areas of dragon fruits in China. The collected roots were visually scored by gall index to evaluate the distribution and severity of diseases caused by Meloidogyne. Then, the isolated nematodes were further confirmed by a combination of morphological and molecular analysis. This survey revealed that the root-knot nematodes were widely distributed in red dragon fruit planting areas in Hainan and caused severe symptoms including stunting, wilting, and yellowing of the stems. The nematode populations were identified as M. enterolobii and M. javanica, among which, M. enterolobii accounted for a larger proportion, 93.9%. To our knowledge, this is the first report of M. enterolobii causing diseases on red dragon fruit. The results obtained from this survey will provide an insight into the presence of root-knot nematodes in dragon fruit plants. Also, these results will raise attention for developing effective management strategies to prevent further spread of root-knot nematodes on dragon fruit in Hainan.